2017
DOI: 10.1097/aog.0000000000002249
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Based Bundles and Cesarean Delivery Surgical Site Infections

Abstract: Evidence-based bundles are associated with a significant reduction in surgical site infection after cesarean delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(31 citation statements)
references
References 50 publications
3
27
1
Order By: Relevance
“… 9 , 10 In a systematic review and meta-analysis of 44 studies, Martin et al 11 found similar surgical site infection reduction when preoperative antibiotic prophylaxis, vaginal preparation and spontaneous removal of the placenta were standardly performed. Carter et al 12 also demonstrated that evidence-based bundles were associated with reduced surgical site infection in a systematic review and meta-analysis. Interestingly, the techniques standardized varied among studies, suggesting that the act of bundling or standardization may independently contribute to improved outcomes rather than the specific techniques individually.…”
Section: Why Standardize Cesarean Delivery Surgical Technique?mentioning
confidence: 96%
“… 9 , 10 In a systematic review and meta-analysis of 44 studies, Martin et al 11 found similar surgical site infection reduction when preoperative antibiotic prophylaxis, vaginal preparation and spontaneous removal of the placenta were standardly performed. Carter et al 12 also demonstrated that evidence-based bundles were associated with reduced surgical site infection in a systematic review and meta-analysis. Interestingly, the techniques standardized varied among studies, suggesting that the act of bundling or standardization may independently contribute to improved outcomes rather than the specific techniques individually.…”
Section: Why Standardize Cesarean Delivery Surgical Technique?mentioning
confidence: 96%
“…However, we cannot conclude with retrospective observational data whether earlier caesarean delivery could have prevented morbidity, which remains an area for further study. This study's findings are timely given the increasing emphasis and implementation of evidence‐based bundles to decrease surgical site infections, postpartum haemorrhage, venous thromboembolism and endometritis after caesarean delivery . Much of the earlier data characterising chorioamnionitis and its impact on maternal outcomes are now decades old .…”
Section: Discussionmentioning
confidence: 94%
“…The primary outcome was a composite of maternal intrapartum and postpartum morbidities as derived from clinical chart review and ICD‐9‐CM diagnostic codes, which included postpartum transfusion, endometritis, venous thromboembolism, hysterectomy, intensive care unit (ICU) admission, death, wound infection/separation for caesarean delivery, and perineal wound infection for vaginal delivery. These adverse maternal outcomes were selected because they have been shown to be associated with maternal infection in previous reports, and recently have been emphasised as part of evidence‐based bundles to decrease surgical site infections, postpartum haemorrhage, venous thromboembolism and endometritis . Adverse outcomes included in this study are currently under consideration for inclusion as part of a standardised core outcome set for maternal infectious outcomes after caesarean delivery by The COMET (Core Outcome Measures in Effectiveness Trials) Initiative.…”
Section: Methodsmentioning
confidence: 99%
“…They account for 14 to 16% of all hospital-acquired infections. With cesarean section (CS) rates rising (187)(188)(189)(190), the risk of surgical site infections is also subject to an increased frequency despite the use of prophylactic antibiotics, with the rate ranging between 2% and 15% (191)(192)(193)(194)(195)(196)(197). MRSA has caused a larger number of severe postpartum infections, especially after CS (198)(199)(200).…”
Section: Clinical Application In Obstetrics and Gynecologymentioning
confidence: 99%